2020
DOI: 10.1089/photob.2019.4766
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation Therapy to Mitigate Radiation Fibrosis Syndrome

Abstract: Objective: We evaluated the role of photobiomodulation (PBM) in radiation fibrosis syndrome (RFS). Background: Radiation therapy (RT) is an important treatment utilized in over half of newly diagnosed cancers. Despite its benefits, patients treated with RT may experience acute and chronic significant side effects depending on both treatment-and patient-related factors. RFS is an important long-term side effect of RT, which can adversely impact patient's quality of life and organ function. With improved oncolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
2
1
0
Order By: Relevance
“…9,[30][31][32][33][34] Besides, PBM has been reported to alleviate radiation fibrosis syndrome caused by cancer radiation therapy. 35 Consistent with these reports, our study confirmed that PBM improved endometrial fibrosis in IUA rats in vivo and TGF-β1induced ESCs fibrosis in vitro. In addition, re-epithelialization of the endometrium is essential for its recovery following pathological injury and scar-free repair after a physiological menstrual breakdown in humans.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…9,[30][31][32][33][34] Besides, PBM has been reported to alleviate radiation fibrosis syndrome caused by cancer radiation therapy. 35 Consistent with these reports, our study confirmed that PBM improved endometrial fibrosis in IUA rats in vivo and TGF-β1induced ESCs fibrosis in vitro. In addition, re-epithelialization of the endometrium is essential for its recovery following pathological injury and scar-free repair after a physiological menstrual breakdown in humans.…”
Section: Discussionsupporting
confidence: 91%
“…According to previous reports, red and infrared PBM could reduce tissue fibrosis in the lungs, kidneys, skin, pulp, muscles, and tendons 9,30–34 . Besides, PBM has been reported to alleviate radiation fibrosis syndrome caused by cancer radiation therapy 35 . Consistent with these reports, our study confirmed that PBM improved endometrial fibrosis in IUA rats in vivo and TGF‐β1‐induced ESCs fibrosis in vitro.…”
Section: Discussionsupporting
confidence: 90%
“…The available evidence demonstrates that PBM can regulate the main targets of the fibrosis pathway ranging from the reduction of the fibroblast proliferation and migration speed, inhibition of the production of TGF-β and the related pathway, to the downregulation of the production and deposition of collagen ( 247 ). There are currently no published clinical studies using PBM to address RIF ( 250 ). Currently, investigators at New York University are evaluating the feasibility, safety, and tolerability of providing PBM for the treatment of RIF in HNC patients treated with RT.…”
Section: Resultsmentioning
confidence: 99%